2006
DOI: 10.1101/gad.1461306
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal tail of the Hedgehog receptor Patched regulates both localization and turnover

Abstract: Patched (Ptc) is a membrane protein whose function in Hedgehog (Hh) signal transduction has been conserved among metazoans and whose malfunction has been implicated in human cancers. Genetic analysis has shown that Ptc negatively regulates Hh signal transduction, but its activity and structure are not known. We investigated the functional and structural properties of Drosophila Ptc and its C-terminal domain (CTD), 183 residues that are predicted to reside in the cytoplasm. Our results show that Ptc, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
134
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(144 citation statements)
references
References 54 publications
10
134
0
Order By: Relevance
“…Previous studies have revealed that the carboxy-terminal cytoplasmic domain of Patched plays an essential role in blocking HH signalling in wing disc [13], as well as regulating Patched degradation and trafficking [14] in Drosophila. mes encodes a mutant PTCH1 protein lacking most of the carboxy-terminal 220 amino acids [13] and is considered a hypomorphic allele.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the carboxy-terminal cytoplasmic domain of Patched plays an essential role in blocking HH signalling in wing disc [13], as well as regulating Patched degradation and trafficking [14] in Drosophila. mes encodes a mutant PTCH1 protein lacking most of the carboxy-terminal 220 amino acids [13] and is considered a hypomorphic allele.…”
Section: Introductionmentioning
confidence: 99%
“…Among these regulated genes in the third instar wing disc is ptc, which is expressed in a band of approximately five to seven cells along the A/P border (Capdevila et al, 1994a;Mullor et al, 1997). Ptc is a Hh receptor (Lu et al, 2006;Marigo et al, 1996;Stone et al, 1996). dpp, another target, is expressed in a band of as many as five to six cells that is displaced from the border by approximately two to three cells (Raftery et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies showing that Shhinduced activation of Hh signaling results in internalization of Shh-bound Ptch (14,47) questions this prediction, because loss of membrane-associated Ptch should also result in loss of secretion of Smo-activating molecules. Therefore, it rather seems feasible that Ptch may secrete a negative regulator of Smo activity.…”
Section: Discussionmentioning
confidence: 97%
“…The SSD is essential for the function of Ptch (13). According to the oligomeric structures of SSD transporters Ptch proteins form stable trimers (14). Thus, it is tempting to speculate that Ptch is a multisubunit transporter whose activity indirectly regulates the function of Smo, e.g.…”
mentioning
confidence: 99%